Cultural mega-events in heritage-rich cities - Jones, Zachary Mark (2021)
The European Capital of Culture (ECoC) is a well-known and long-standing European policy that annually awards the title of Capital to two or more cities that deliver cultural initiatives throughout one year of celebrations. The programme has been hosted by over 60 cities throughout Europe during the last 35 years. Some host cities have used the ECoC to develop large projects that contribute to urban rebranding and regeneration (e.g. the facilities on the new waterfront of Marseille, made for the 2013 ECoC) and, more frequently, projects that adapt existing facilities and places, or smaller scale and less spectacular interventions in the city fabric. As a wide variety of differing cities have hosted the event, the ECoC has contributed to urban transformations at different scales, often with particular reference to historic and heritage-rich settings, but also brings about long-term effects in terms of cultural facilities and venues, tourism appeal and even the intangible heritage narratives attached to places. Drawing on the HOMEE Research Project and on recent publications by the authors, this paper discusses the range of large-to-small-scale planning, the (re)generation of cultural facilities and places in historic cities and heritage-rich areas to accommodate cultural mega-events and the effects they have on host cities over time. In the conclusions, the paper expands beyond the ECoC (in the direction of sport mega-events) to consider and highlight forthcoming challenges for urban policy-making and the planning of mega-events in Europe.